Pengaruh SEO (Search Engine Optimization) Dalam Strategi Pemasaran Digital : Studi Kasus Pada Sambal Gerilya di Platform Shopee - Sembiring, Erika Dafrina; Hasibuan, Ali Fikri (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2024)
This study aims to determine the influence of Search Engine Optimization in the Digital Marketing Strategy Case Study on Guerrilla Sauce on the Shopee Platform. Mixed methods research is a type of research in which a researcher or research team combines elements of qualitative and quantitative research approaches (e.g., the use of qualitative and quantitative viewpoints, data collection, analysis, and inference techniques). From the results of the study, it was concluded that the Search Engine Optimization (X) variable had a positive and significant effect on the Digital Marketing Strategy (Y) of the Guerrilla Sambal on the Shopee Platform. Based on the results of the research, it was found that the Search Engine Optimization variable had a positive and significant effect on the Digital Marketing Strategy Case Study on the Guerrilla Sambal on the Shopee Platform. With a count value of 17.646> the table is 1.985 with a significance value of 0.000< 0.05. And Sambal Guerrilla also emphasizes SEO and content marketing strategies to deepen its market penetration.